2020
DOI: 10.3390/catal10080865
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Metal Doping Effects on Co3O4 Catalysts for the Total Oxidation of Toluene and Propane

Abstract: Metal-doped (Mn, Cu, Ni, and Fe) cobalt oxides were prepared by a coprecipitation method and were used as catalysts for the total oxidation of toluene and propane. The metal-doped catalysts displayed the same cubic spinel Co3O4 structure as the pure cobalt oxide did; the variation of cell parameter demonstrated the incorporation of dopants into the cobalt oxide lattice. FTIR spectra revealed the segregation of manganese oxide and iron oxide. The addition of dopant greatly influenced the crystallite size, strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Compared with pure Co 3 O 4 , the Raman bands of the x % CeÀ Co 3 O 4 samples are more weak and broad because of the incorporation of Ce into the Co 3 O 4 lattice, resulting in lattice expansion and lattice distortion, as revealed by XRD analysis. [16] With the increase of Ce content, the intensity of band at ∼ 465 cm À 1 where corresponds to the Raman active F 2g mode of cubic fluorite type CeO 2 [17] becomes higher, indicating the formation of CeO 2 for the x % CeÀ Co 3 O 4 samples.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Compared with pure Co 3 O 4 , the Raman bands of the x % CeÀ Co 3 O 4 samples are more weak and broad because of the incorporation of Ce into the Co 3 O 4 lattice, resulting in lattice expansion and lattice distortion, as revealed by XRD analysis. [16] With the increase of Ce content, the intensity of band at ∼ 465 cm À 1 where corresponds to the Raman active F 2g mode of cubic fluorite type CeO 2 [17] becomes higher, indicating the formation of CeO 2 for the x % CeÀ Co 3 O 4 samples.…”
Section: Resultsmentioning
confidence: 94%
“…Compared with pure Co 3 O 4 , the Raman bands of the x % CeÀ Co 3 O 4 samples are more weak and broad because of the incorporation of Ce into the Co 3 O 4 lattice, resulting in lattice expansion and lattice distortion, as revealed by XRD analysis. [16] With the increase of Ce content, the intensity of band at ∼ 465 cm À 1 where corresponds to the Raman active F 2g mode of cubic fluorite type CeO 2 [17] becomes higher, indicating the formation of CeO 4b) reveals two major peaks with binding energy at ∼ 779.6 and ∼ 794.6 eV with a spin energy separation of 15 eV, corresponding to the Co 2p 3/2 and Co 2p 1/2 , respectively. [18] In detail, the Co 2p 3/2 peak can be divided into two peaks, which is ascribed to Co 3 + (∼ 779.6 eV) and Co 2 + (∼ 781.1 eV) respectively.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Cai et al demonstrated that Mn introduction leads to increased surface Co 2+ concentration and active oxygen, which contributed to high catalytic activity in VOC oxidation (Cai et al, 2015). In a recent study (Zhang et al, 2020), the introduction of Mn increased reducibility and catalytic performance of cobalt oxides. The Co-Mn oxide catalysts were more active in toluene oxidation than their Co-Ni or Co-Cu analogues.…”
Section: Introductionmentioning
confidence: 99%